KAMI DAN YOUKAI DALAM KOMIK KAMISAMA HAJIMEMASHITA KARYA SUZUKI JULIETTA - Putri Wisundari, Ni Made (Humanis, 2016)
This research entitles “Kami and youkai in Kamisama Hajimemashita by Suzuki Julietta”. The reason for this title was choosen is because Kamisama Hajimemashita manga consist of aspect that related to Kami and Youkai forms and myths . The purpose of this research is to know the forms and myths of kami and youkai that contained in Kamisama Hajimemashita m anga. The Method used for this research is Descriptive Analysis and Informal Method. The theory used is Anthropology Literature Theory and Semiotics Theory by Marcel Danesi. As the result, kami that contained in the Kamisama Hajimemashita manga are Tochigami , Raijin, Fuujin, Oo kuninushi no Kami, Izanami, and Ikusagami. Youkai that contained in Kamisama Hajimemashita manga are kitsune, tengu, and ryuu ou. They have human form , human characteristic and also have their own duties. There are some Japanese myth in the Kamisama Hajimemashita manga. First, myth about snake as kami’s servant; second, myth is about kami and youkai dwelling; third myth is about Ookuninushi no Kami as owner of Izumo Taisha,the fourth myth is about kami’s conference and the last myth is about Izanami as ruler of yomi no kuni.
Keywords: Kami, Youkai, Anthropology Literature